Carbohydrate-Free Peach (Prunus persica) and Plum (Prunus salicina) [corrected] Juice Affects Fecal Microbial Ecology in an Obese Animal Model. - Noratto, Giuliana D.; García Mazcorro, José Francisco; Markel, Melissa; Martino, Hercia S.; Minamoto, Yasushi; Steiner, Jörg M.; Byrne, David; Suchodolski, Jan S.; Mertens Talcott, Susanne U. (Public Library of Science, 2014)
BACKGROUND